The Meaning of Kadyatmikan in the Tutur Tegesing Wisik Warah Text: A Study of Cultural Semiotics - Mahardika, Ida Bagus Pradnyana; Putra, Ida Bagus Rai; Laksminy, Luh Putu (Humanus, 2025)
Kadyatmikan, a core aspect of Balinese spiritual teachings, is a secondary modeling system that offers guidance toward spiritual balance and moksa (liberation) through practices such as self-control, meditation, and harmony with nature. This study investigates the meaning of Kadyatmikan in the Tutur Tegesing Wisik Warah text, through Yuri Lotman's (1990) cultural semiotics framework. Using a descriptive qualitative method, this research identified and analyzed the symbolic elements and spiritual codes within the text. A heuristic reading method was applied to uncover surface-level meanings, such as narrative structures and linguistic features, and connotative reading to explore deeper symbolic and cultural interpretations. The analysis focused on the interaction of these elements with the Balinese cultural semiosphere. The findings highlight the symbolic relevance of teachings like Sad Ripu and Yoga (meditative practices), demonstrating their role in fostering self-realization and cultural identity. Discussion emphasizes the dual function of these teachings: preserving Balinese spiritual values and addressing contemporary challenges through cultural adaptability. The research contributes to empirical studies of cultural semiotics and conceptual explorations of traditional wisdom in modern contexts